The Effects of a Parenting Program on Maternal Well-Being: Evidence from a Randomized Controlled Trial - Georg F. Camehl; Christa Katharina Spiess; Kurt Hahlweg (The B.E. Journal of Economic Analysis & Policy, 2020)
This paper evaluates how a light-touch parenting program for parents of children below school entry age affects maternal family well-being. We analyze data from a randomized controlled trial focusing on non-disadvantaged parents. Overall, results show no short-term effects but a relatively large positive effect of the intervention on maternal family well-being in the medium term. With a 20- to 30-percent standard deviation, the effects appearing three years after treatment are relatively large. Mechanisms such as improvements in child behavior are further explored.
Keywords: I31; I26; J13; C21; C26; 300; parenting program; family well-being; randomized controlled trial; Triple P